Estrategy and cognition: the strategy execution process through cognitive alignment (2019)
The alternative-generating processes and strategic decision making are results of mental maps subjectively built by decision makers and executors. The different agents of the organization, understood as a socio-technical complexity, decide and act through mental maps used to “read” the reality. The alignment of these mental maps, that is based on convergent communication, contributes to reduce cognitive dispersion in the agents and, becomes the key to strategy execution and organizational learning.